4
$\begingroup$

I am trying to find the value of $t$ where the graph of the following parametric equations crosses itself: \begin{align} x =&\; t^3 − t + 3\\ y =&\; t^2 − 3 \end{align} I know that the next step toward solving this problem involves creating two parallel equations with a different kind of variable.

The result will look like:

\begin{align} t^3 - t + 3 = s^3 - s + 3 \tag1\\ t^2 - 3 = s^2 - 3 \tag2 \end{align}

After this point, I am totally stumped. I know that I will have to solve for $t$, and it looks like doing so will involve some skill I have not yet acquired. Multiplying (2) by $-t$ and adding (1) to (2) helps me to eliminate the $t^3$, but I am left with

$$s^3 - s(t^3) - (s^2)t + t = 0 $$

an equation for which I have no idea how to solve for $t$.

Could someone please show me how to find $t$-values at the point(s) where the graph from these equations crosses itself? Thanks in advance!

$\endgroup$
2
  • 1
    $\begingroup$ x does not equal y where this parametric equation crosses itself! @probably_someone $\endgroup$
    – Dan Sp.
    Apr 2 '18 at 23:10
  • $\begingroup$ Wow, yeah, that was bad. Sorry. $\endgroup$ Apr 2 '18 at 23:13
2
$\begingroup$

Solving for $t$ from $y=t^2-3$ we get $t=\pm \sqrt{y+3}$. Substituting this into $x = t^3 − t + 3$ we get $$x = (y+3)^{(3/2)}-\sqrt{y+3}+3\quad\text{and}\quad x = -(y+3)^{(3/2)}+\sqrt{y+3}+3.$$ These two functions (which are only defined for $y\ge-3$) intersect at $$ y=-3\quad\text{and}\quad y=-2.$$ Substituting these back into the equations for $x$ we get $$x=3.$$ Since the functions are undefined for $y<-3$, $(3,-3)$ is a connection point, not a crossing. The only crossing is, therefore at $(3,-2)$.

$\endgroup$
2
$\begingroup$

It crosses itself where, for two different values of t, you get equal x and y values. So letting $t_1 = u$ and $t_2=v$: $$u^3-u+3 = v^3-v+3$$ $$u^2-3 = v^2-3$$ These simplify to: $$u(u^2-1) = v(v^2-1)$$ $$u^2 = v^2$$ We know we want u and v to be different. From the second equation, we can deduce that $u = -v$. Plug this into the first equation: $$-v^3+v+3 = v^3-v+3$$ or $$2v^3-2v=0$$ $$v(v^2-1)=0$$ $v=0$ would make $u=0$ which disqualifies it so: $$v^2-1 = 0$$ $v\pm 1$ and $u\mp 1$ then are the two values of t where the parametric equation crosses itself.

Plug $t=1$ and $t=-1$ into your equations for x and y and you will see this is true.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.